Evaluation of the VAT Exemption Facility Policy for Universities Reviewed from the Cost of Compliance - Rahmat Ikhsan Juandano; Prianto Budi Saptono (Publikasi Indonesia, 2025)
To optimize state revenue, the Indonesian government continues to implement tax extensification and intensification programs. Under Law Number 7 of 2021 (Harmonization of Tax Regulations Law or UU HPP), educational services are reclassified as Value-Added Tax (VAT) objects with exemption facilities, requiring universities and other educational service providers to register as Taxable Firms (PKP). This regulatory change obliges them to administer VAT invoices without the right to credit input tax, which was not the case under the previous regulation where educational services were categorized as non-VAT objects. As a result, this policy significantly increases the compliance cost for educational institutions. The objective of this study is to examine the rise in compliance costs—specifically direct monetary costs, time costs, and psychological burdens—experienced by educational service providers due to the VAT regulation changes. This research adopts a qualitative approach through literature review and comparative analysis with international best practices in other countries that apply VAT to education. The findings reveal that although the VAT exemption facility aims to maintain accessibility, the administrative burden placed on educational institutions has increased, particularly in relation to invoice issuance, system adjustments, and internal training. These factors contribute to higher operational costs and stress levels among administrative personnel. The study highlights the need for clearer technical guidelines and support systems to reduce compliance burden. It also provides insights for policymakers in balancing fiscal objectives with the operational realities of the education sector.